This equation is euler-cauchy equation.
Substitute "y=x^{\\lambda}" into the homogenous equation
"x^2(x^\\lambda)''+x(x^\\lambda)'-x^\\lambda=0"
"\\lambda(\\lambda-1)x^\\lambda+\\lambda x^\\lambda- x^\\lambda=0"
"\\lambda^2-1=0; \\lambda=\\pm1"
Hence the solution of the homogenous equation
"y=c_1x+c_2x^{-1}"
Using method of variations of parameters ("c_1=c_1(x);c_2=c_2(x)" ) will give us the system
"\\begin{matrix}\n c_1'x+c_2'x^{-1}=0 \\\\\n c_1'-c_2'x^{-2}=e^x \n\\end{matrix}\\implies\n\\begin{matrix}\n c_1'=c_2'x^{-2}+e^x \\\\\n xe^x+c_2'x*x^{-2}+c_2'x^{-1}=0 \n\\end{matrix}"
"c_2'x^{-1}=-xe^x\\implies c_2'=-\\frac{1}{2}x^2e^x"
"c_2=-\\frac{1}{2}e^x(x^2-2x+2)"
"c_1'=-\\frac{1}{2}x^2e^x*x^{-2}+e^x=\\frac{1}{2}e^x"
"c_1=\\frac{1}{2}e^x"
Therefore
"y=c_1x+c_2x^{-1}+\\frac{1}{2}xe^x-\\frac{1}{2}x^{-1}e^x(x^2-2x+2)"
Comments
Leave a comment